Reality shows musicais: do corpo-candidato ao corpo-commodity - Almeida, Erika Silva e Souza de (2018)
The growing success of musical reality shows over the last 20 years is linked to the reconfiguration of television as an agent and mediatic center of the music industry. This research takes as its object the musical reality shows, with corpus as The Voice USA. The objective is to investigate the role of bodies that present themselves in the legitimization of cultural consumption patterns in the music market and, to that end, will find itself in a kind of 'molding process' of the body in a pattern produced not only to musical point of view, but also to several other segments, composed by costumes, makeup, stage performance (theatricality) and choreography (dance). The hypothesis is that biopolitics applied by the program and improved over the course of their seasons turn bodies-candidates into bodies-commodities, intervening directly in the music industry and the markets it involves. The research will be based, above all, on the concept of biopolitics, by Michel Foucault (2008); in the concept of convergence and connection, by Henry Jenkins (2008, 2014); in the Corpomedia Theory, by Katz and Greiner; in the control society, by Gilles Deleuze (2013); and in the concepts of public and opinion, by Gabriel Tarde (2005). The methodology will use the bibliographic review and a field research in the corpus, formed by two seasons of the program